Modelling of last hypothesis of climate change impacts on water resources in Sierra de las Cabras aquifer (Southern Spain) - Jiménez Fernández, Pedro; Jiménez-Gavilán, Pablo (My University, 2015)
Having models that reflect the reality of a system operation becomes critical to the effec-tive management of water resources in a watershed, especially considering the different scenes of climate change predicted for the Mediterranean regions by the Intergovernmen-tal Panel on Climate Change (IPCC). The fifth Assessment Report of IPCC (AR5) esti-mates an increase in average temperatures and a precipitation decrease between 10 and 20% for Mediterranean region which could generate drought events in the study area. The present research tries to determinate the potential impacts that climate change may have on water resources. The Sacramento model has been used to model the water resources of an inertial aquifer, Sierra de las Cabras. In turn, IPCC forecasts of climate change for the study area (Mediterranean region) have been simulated taking into account the degree as-sessing of affection to the water resources opposite to eventual episodes of drought, and the social and environmental implications that will result have been also determined.
Keywords: Clima - Cambios; Acuíferos; Southern Spain; Climate Change; Water resources; Carbonatic aquifer